Playgrounds of political imprisonment: historical narratives of sport on Robben Island, 1962–1990 - Mitchell, Vanessa Jacqueline (Stellenbosch : Stellenbosch University, 2025)
Thesis PhD (Sport Sc)--Stellenbosch University, 2025.